Negotiating Political Spaces: Social and Environmental Activism in the Chinese Countryside - Maria Bondes (German Institute of Global and Area Studies (GIGA), 2011)
The proliferation of social organizations in China has engendered a lively debate about how to conceptualize these social forces. This paper argues that such a conceptualization should take into account the role that both the party-state and social actors attribute to social organizations. With an empirical case study from the western Chinese countryside, this paper explores how social organizations both adapt to the restrictive authoritarian framework and negotiate the spaces opening up to society in the realms of environmental and social politics. The study shows that while the party-state understands organizations as consultants and partners in service provision, they have a deviating self-image with the Western concepts of NGO and civil society becoming increasingly relevant as frames of reference. While their practices remain within the limits imposed by the authoritarian framework, they impact policy formulation, local political participation, and the formation of social networks according to their own self-image as members of a budding Chinese civil society.
Keywords: 300; China; civil society; NGO; social organizations; Nichtregierungsorganisation; Bürgerbeteiligung; Gesellschaft; Sozialer Wandel; China